2007
DOI: 10.1159/000098660
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Leucocyte Antigen DQ in the Presentation of T Cell Epitopes in the Major Cow’s Milk Allergen αs1-Casein

Abstract: Background: Little is known about the association between human leucocyte antigen (HLA) and cow’s milk allergy (CMA). The aim of the present study was to determine the HLA restriction of T cell clones (TCCs) specific to αs1-casein, the most abundant milk protein, and to study possible HLA class II allele associations with CMA. Methods: αs1-Casein-specific TCCs were derived from 6 children with CMA, 9 atopic children without CMA and 5 non-atopic children. T cell epitope specificity was defined by stimulation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
(46 reference statements)
1
12
1
3
Order By: Relevance
“…A variety of antigen-presenting HLA molecules could thus be expected to be involved in CMA. Studies on CM-specific T-cell clones from CMA patients indicated that antibodies to HLA-DR, HLA-DQ and HLA-DP could all restrict the proliferation of T-cell clones [37,38]. Therefore, it is apprehensible that an earlier study [8] as well as the present study detected no association between CMA and HLA haplotypes.…”
Section: Discussioncontrasting
confidence: 45%
“…A variety of antigen-presenting HLA molecules could thus be expected to be involved in CMA. Studies on CM-specific T-cell clones from CMA patients indicated that antibodies to HLA-DR, HLA-DQ and HLA-DP could all restrict the proliferation of T-cell clones [37,38]. Therefore, it is apprehensible that an earlier study [8] as well as the present study detected no association between CMA and HLA haplotypes.…”
Section: Discussioncontrasting
confidence: 45%
“…Furthermore, a consistent number of the studies investigating the immune responses to CMP, and to food allergens in general, have used T-cell lines or T-cell clones, mostly derived from peripheral blood mononuclear cells (PBMCs) (5)(6)(7)(8)(9)(10)(11)(12). Albeit these are powerful techniques to investigate immune response to several antigens, and to define the stimulatory sequences in complex antigenic proteins, manipulation can occur in long-term cell cultures that could result in alteration of cell phenotypes and functions.…”
mentioning
confidence: 99%
“…Во-первых, ␣S1 фракция казеина присутствует как в коровьем, так и в козьем молоке [4,15], при этом соотношение ␣S1 и ␣S2 фракции казеина генетиче-ски детерминировано и колеблется в довольно широких пределах [16,17]. Во-вторых, ␣S1-и ␣S2-казеин (как козьего, так и коровьего молока) относятся к мажорным аллергенам [18,19] и не отличаются по своей аллерген-ности [4]. Кроме того, у пациентов с персистирующей аллергией выявляются IgE-антитела к эпитопам как ␣S1-, так и ␣S2-казеина [20,21].…”
Section: при легких проявлениях пищевой аллергии у детей назначение эunclassified